Penalty For Constitutional Violations - Reaibin Salam Mohammed; Aram Nabee Mohammed; Salar Swar Ismael (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The purpose of this research is critical analyzing the penalty for constitutional violations. States have different perspective about the breaching of constitution and determining sentence for constitutional violators. In this paper, we depend on qualitative method by using case studies and comparing with each other. This legal paper divided into two parts. In the first part, Unconstitutional and Outlawed Political Parties will be argued by focusing on some cases in German and Turkey that related to violating their constitutions. In the second part, violating the constitution by government and parliament will be analyzed, for this purpose, the referendum of Kurdistan region and Catalans region as violation of constitution will be debated. Finally, the question is there any legal punishment for constitutional violations? Will be considered.